1990
DOI: 10.6028/nist.ir.89-4205
|View full text |Cite
|
Sign up to set email alerts
|

Potential methods for measuring and detecting lead in existing paint films:

Abstract: Recent legislation required the U.S. Department of Housing and Urban Development (HUD) to establish procedures to eliminate, as far as practicable, the hazards of lead-based paint poisoning in any existing HUD-controlled housing. Thus, HUD promulgated a regulation which requires abatement to eliminate lead-based paint poisoning hazards in housing in which the concentration of lead in paint equals or exceeds 1 mg/cm^. The legislation also required HUD to review test methods for measuring lead in paint. The Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The literature was also reviewed for potential measurement methods for lead in paint [11]. Each method was evaluated on the basis of the following essential criteria: reliability, safety, and accuracy and precision.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature was also reviewed for potential measurement methods for lead in paint [11]. Each method was evaluated on the basis of the following essential criteria: reliability, safety, and accuracy and precision.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…From the literature review [11], it was concluded that measurement procedures based upon the use of some portable XRF analyzers could meet the essential and desirable criteria cited above. Currently, both K and L x-ray analyzers are available.…”
Section: Portable Xrf Analyzersmentioning
confidence: 99%